2020
DOI: 10.1002/jha2.7
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of toxicities related to hydroxycarbamide dosing strategies

Abstract: Due to fear of short‐term toxicities, there is nonconsensus of hydroxycarbamide dosing strategy (escalated vs fixed‐dosing methods), which contributes to its suboptimal use. We performed a meta‐analysis to summarize the incidence rates of toxicities associated with both dosing methods. Summarized incidence rates could not be statistically compared between dosing methods due to sparse data. Summarized neutropenia and thrombocytopenia incidence rates were slightly higher when using escalated dosing than with fix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Regarding hydroxyurea toxicity, a meta-analysis found that neutropenia was more frequent with MTD dosing. 14 We noted increased neutropenia without an increase in significant infection in the intensive dose arm.…”
mentioning
confidence: 67%
“…Regarding hydroxyurea toxicity, a meta-analysis found that neutropenia was more frequent with MTD dosing. 14 We noted increased neutropenia without an increase in significant infection in the intensive dose arm.…”
mentioning
confidence: 67%